Influence of Country Factors on Entry Mode Through Knowledge and Transactional Cost Economics: Market Entry: Evidence from Construction Firms - Yasmeen, Kausar; Viswanathan, Kuperan (International Journal of Economics and Financial Issues, 2017)
Owing to the competition global level economy of world and pattern are promoting to the construction firms to increase into emerging economies. Entry mode has become important for firms. The present paper aims to explore the entry modes which are preferred by construction firms in Malaysia, for their international projects, on whether construction firms choose equity modes, non-equity modes or both modes. 19 questionnaires were filled by respondents by using cross-sectional data technique. This study found that country specific factors (cultural differences and target country risk) influence the entry mode of firms directly and through knowledge and transactional cost economics by applying the multinomial logistic regression. This study contributes theoretically and practically along with this; present study recommends that government should improve internal and external factors to enter the firms for economic development. Keywords: Entry Mode, External Factors, İnternal Factors Emerging Economy JEL Classifications: M, M5, M21